PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENJUALAN ROKOK ILEGAL OLEH BEA DAN CUKAI KABUPATEN INDRAGIRI HILIR BERDASARKAN UNDANG-UNDANG NOMOR 39 TAHUN 2007 TENTANG CUKAI - MEGAWATI, RUTH; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cigarettes are one of the items subject to excise. Illegal smoking is a favorite and sought after by many people compared to legal cigarettes in the area of Tembilahan City. The purpose of this thesis is: First, the impact of illegal cigarette sales crime in the city of Tembilahan, Indragiri Hilir Regency, Second, Law enforcement against criminal acts of illegal cigarette sales by Customs and Excise of Indragiri Hilir Regency, Third, Barriers and efforts in law enforcement against criminal sale of illegal cigarettes by the Customs and Excise of Indragiri Hilir Regency.This type of research can be classified in the type of sociological juridical research, because in this study the author directly conducts research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted in Tembilahan City, while the population and sample were all parties related to the problem under study in this study, the data sources used were primary data, secondary data and tertiary data and data collection techniques in this observation study. interviews and literature reviews.From the results of this study there are three main things that can be concluded, namely: First, The impact of illegal cigarette sales is loss of income for the State and health problems for the community. Second, Law Enforcement in dealing with criminal acts of selling illegal cigarettes in the form of preventive law enforcement can be in the form of conducting legal counseling, carrying out observations and conducting patrols, market operations in accordance with existing regulations. Third, barriers faced in law enforcement against criminal acts of illegal cigarette sales are 2 (two) factors, namely internal factors that become obstacles, including lack of personnel, lack of operational facilities. While the External factors include geographical location and lack of community role. Meanwhile, the efforts made in overcoming barriers to law enforcement criminal acts of illegal cigarette sales are adding personnel and adding operational facilities. Suggestion, First, the community should be aware of the law. Second, law enforcement carried out by the authorities should be in accordance with the rules. Third, in overcoming obstacles, the apparatus should attempt to be professional and follow the rules and regulations.Keywords: Crime - Sales - Illegal Cigarettes